2020
DOI: 10.1093/nar/gkaa686
|View full text |Cite
|
Sign up to set email alerts
|

Genome maintenance functions of a putative Trypanosoma brucei translesion DNA polymerase include telomere association and a role in antigenic variation

Abstract: Maintenance of genome integrity is critical to guarantee transfer of an intact genome from parent to offspring during cell division. DNA polymerases (Pols) provide roles in both replication of the genome and the repair of a wide range of lesions. Amongst replicative DNA Pols, translesion DNA Pols play a particular role: replication to bypass DNA damage. All cells express a range of translesion Pols, but little work has examined their function in parasites, including whether the enzymes might contribute to host… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 94 publications
3
16
0
Order By: Relevance
“…Samples were then cooled on ice and the supernatant was harvested and diluted with NuPAGE LDS sample buffer (ThermoFisher) and dithiothreitol to a final concentration of 1× sample buffer with 100 mM dithiothreitol. Harvested proteins were denatured at 70°C for 10 min and then frozen before processing for mass spectrometry using the protocol described in ( 40 ).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were then cooled on ice and the supernatant was harvested and diluted with NuPAGE LDS sample buffer (ThermoFisher) and dithiothreitol to a final concentration of 1× sample buffer with 100 mM dithiothreitol. Harvested proteins were denatured at 70°C for 10 min and then frozen before processing for mass spectrometry using the protocol described in ( 40 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although PolIE was previously identified in a pull-down using a telomere oligo and in a TbTRF IP (48), it has not been directly confirmed that PolIE is a telomere protein (48,49). To verify that PolIE is indeed an intrinsic component of the telomere complex, we first C-terminally tagged one POLIE endogenous allele with 13x myc in the bloodstream form (BF, the mammalian infectious stage) T. brucei cells where one TbTIF2 endogenous allele is C-terminally tagged with an F2H epitope (Fig.…”
Section: T Brucei Dna Polymerase Ie Associates With the Telomere Chromentioning
confidence: 97%
“…1A). Among these, DNA polymerase IE (Tb927.11.5550) (48,49) is one of the most abundant proteins. In addition, we have identified TbTRF (36), TbTIF2 (42), TbRAP1 (37), NUP98, NUP96, NUP152, SMC1, SMC3, SMC4, PPL2 (48), and TelAP1 (48), all core histones, H3v, and H2Bv, etc.…”
Section: Identify T Brucei Telomere Components By Pich and Tbtrf/tbtimentioning
confidence: 99%
See 2 more Smart Citations